Gender Stereotypes and Androgyny in Contemporary Fiction: A Literary Analysis of Emily Henry’s Book Lovers (2022) (PANOPTICON: Journal of English Studies, 2025)
This study analyzes the issue of gender stereotypes as reflected in three characters from Emily Henry’s novel Book Lovers (2022). Employing a qualitative approach, the research focuses on describing and interpreting the characters' behaviors, personality traits, and social roles to uncover how gender expectations are constructed and challenged within the narrative. The analysis is grounded in Sandra Bem’s Gender Schema Theory (1981), which provides a framework for understanding how individuals internalize and perform gender roles based on societal norms. The findings reveal that the novel portrays a range of gendered traits—femininity, masculinity, and androgyny—across both male and female characters. The main character, Nora Stephens, in particular, subverts traditional gender stereotypes by embracing traits typically associated with masculinity, such as ambition and assertiveness, while also engaging with her emotional and relational self. Meanwhile, male characters are shown to exhibit qualities traditionally coded as feminine, such as empathy and vulnerability. Ultimately, the study concludes that Book Lovers presents a nuanced exploration of gender identity, illustrating how characters can resist and redefine stereotypes. By doing so, the novel supports a more flexible and inclusive understanding of gender, in line with Bem’s concept of androgyny as a path to psychological adaptability and self-development.